2016
DOI: 10.1111/bcp.12861
|View full text |Cite
|
Sign up to set email alerts
|

The effect of LCZ696 (sacubitril/valsartan) on amyloid‐β concentrations in cerebrospinal fluid in healthy subjects

Abstract: AimsLCZ696 (angiotensin receptor neprilysin inhibitor) is a novel drug developed for the treatment of heart failure with reduced ejection fraction. Neprilysin is one of multiple enzymes degrading amyloid‐β (Aβ). Its inhibition may increase Aβ levels. The potential exists that treatment of LCZ696, through the inhibition of neprilysin by LBQ657 (an LCZ696 metabolite), may result in accumulation of Aβ. The aim of this study was to assess the blood–brain‐barrier penetration of LBQ657 and the potential effects of L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 95 publications
(63 citation statements)
references
References 38 publications
1
58
1
3
Order By: Relevance
“…Pojawiają się pewne wątpliwości dotyczące wpływu sakubitrilu/walsartanu na rozkład β-amyloidu w mózgu, który teoretycznie mógłby nasilać powstawanie jego złogów [189][190][191]. Jednak w niedawno opublikowanym małym 14-dniowym badaniu przeprowadzonym wśród zdrowych ochotników wykazano zwiększone stężenie β-amyloidu raczej w postaci rozpuszczalnej niż w postaciach ulegających akumulacji w narządach, co jeśli zostanie potwierdzone w dłuższym czasie u chorych z HFrEF, mogłoby wskazywać na bezpieczeństwo tego leku w odniesieniu do mózgu [192]. Długoterminowe bezpieczeństwo terapii powinno być przedmiotem dalszych badań.…”
Section: Digoksynaunclassified
“…Pojawiają się pewne wątpliwości dotyczące wpływu sakubitrilu/walsartanu na rozkład β-amyloidu w mózgu, który teoretycznie mógłby nasilać powstawanie jego złogów [189][190][191]. Jednak w niedawno opublikowanym małym 14-dniowym badaniu przeprowadzonym wśród zdrowych ochotników wykazano zwiększone stężenie β-amyloidu raczej w postaci rozpuszczalnej niż w postaciach ulegających akumulacji w narządach, co jeśli zostanie potwierdzone w dłuższym czasie u chorych z HFrEF, mogłoby wskazywać na bezpieczeństwo tego leku w odniesieniu do mózgu [192]. Długoterminowe bezpieczeństwo terapii powinno być przedmiotem dalszych badań.…”
Section: Digoksynaunclassified
“…There was an increase in the amyloid-β1–38 isoform which is hydrophilic and does not aggregate to form amyloid plaques. Levels of amyloid-β1–40 and amyloid-β1–42 concentrations in the CSF (which do form amyloid plaques) were unchanged from baseline 45. These and other preclinical studies46 seem to suggest that although NEP inhibition in the brain results in a net increase in total amyloid concentration, the increase is primarily driven by the soluble, non-plaque forming, amyloid-β1–38 isoform.…”
Section: Effects Of Sacubitril/valsartan On Amyloid-βmentioning
confidence: 55%
“…68 This is a hypothetical concern and not based on any human studies: a Chinese study found no association between two NEP gene polymorphisms and Alzheimer's disease in elderly people. 69 Furthermore, a 2-week LCZ696 administration in human healthy volunteers did not modify Abeta 1−40 and Abeta 1−42 levels in the cerebrospinal fluid 70 and no cognition-related adverse events related to treatment have been reported in any of the randomised clinical trials to date, probably because multiple (20) proteins are involved in the clearance of amyloid beta-peptides. There is therefore no conclusive evidence for an association between NEP and Alzheimer's disease in humans.…”
Section: Safety Profile Of Lcz696mentioning
confidence: 89%